Association Between Social Cognition Changes and Resting State Functional Connectivity in Frontotemporal Dementia, Alzheimer’s Disease, Parkinson’s Disease, and Healthy Controls - Multani, Namita; Taghdiri, Foad; Anor, Cassandra J.; Varriano, Brenda; Misquitta, Karen; Tang-Wai, David F.; Keren, Ron; Fox, Susan; Lang, Anthony E.; Vijverman, Anne Catherine; Marras, Connie; Tartaglia, Maria Carmela (Frontiers in Neuroscience, 2019)
Objective: To determine the relationship between alterations in resting state functional connectivity and social cognition dysfunction amongst patients with frontotemporal dementia (FTD), Alzheimer’s disease (AD), Parkinson’s disease (PD) and healthy controls (HC). Methods: Fifty-seven participants (FTD=10, AD=18, PD=19, and HC=10) underwent structural and functional imaging and completed the Awareness of Social Inference Test-Emotion Evaluation Test (TASIT-EET), Behavioral Inhibition System/Behavioral Activation System (BIS/BAS) scale, Revised Self-Monitoring Scale (RSMS), Interpersonal Reactivity Index (IRI), and Social Norms Questionnaire (SNQ). A multi-variate pattern analysis (MVPA) was carried out to determine activation differences between the groups. The clusters from the MVPA were used as seeds for the ROI-to-voxel analysis. Relationship between social cognition deficits and uncinate integrity was also investigated. Results: BOLD signal activation differed amongst the four groups of AD, PD, FTD and HC in the left inferior temporal gyrus-anterior division (L-ITG (ant)), right central opercular cortex (R-COp), right supramarginal gyrus, posterior division (R-SMG, post), right angular gyrus (R-AG), and R-ITG. The BOLD co-activation of the L-ITG (ant) with bilateral frontal pole (FP) and paracingulate gyrus was positively associated with IRI-perspective taking (PT) (r = .38, p = .007), SNQ total (r = .37, p = .009) and TASIT-EET (r = .47, p < .001). Conclusion: Patients with neurodegenerative diseases showed alterations in connectivity in brain regions important for social cognition compared with healthy controls. Functional connectivity correlated with performance on social cognition tasks and alterations could be responsible for some of the social cognition deficits observed in all neurodegenerative diseases.